Analisis Segmen Pasar dan Prilaku Nasabah Bank Syariah: Kajian Hukum Islam Terhadap Produk HSBC Amanah Indonesia - Mursid, Mansur Chadi; Irviana, Rr. Kathrin (Faculty of Shariah and Law, 2012)
The purpose of this research is for identifying market segment and customer behavior toward Islamic banking and its marketing implications in all regions of DKI Jakarta. The analytical tools applied are analysis of cluster, factor, and descriptive. The result of this research for segmentation aspect showed the characteristics and size of each market segment of Islamic banks. The market segment consists of shariah loyalist, floating mass, and conventional loyalist. From this research, floating mass segment is the most potential segment due to its market size compared to shariah loyalist and conventional loyalist segmentsDOI: 10.15408/aiq.v4i2.2097